Global maps of the step-wise topography corrected and crustal components stripped geoids using the CRUST 2.0 model - TENZER, Robert (Contributions to Geophysics and Geodesy, 2009)
We compile global maps of the step-wise  topography corrected and crustal components stripped geoids based  on the geopotential model EGM’08 complete  to spheri- cal harmonic degree 180 and the CRUST 2.0 global  crustal model.  The spectral resolution complete to degree 180 is used to compute the primary indirect bathymetric stripping and topographic eﬀects  on the  geoid,  while  degree  90 for the  primary indirect ice stripping eﬀect.   The  primary indirect stripping eﬀects  of the  soft  and  hard  sediments, and  the upper,  middle  and  lower  consolidated crust  components are  forward  modeled  in spatial form  using  the  2 × 2 arc-deg  discrete data  of the  CRUST  2.0  model.   The  ocean,  ice, sediment and consolidated crust  density contrasts are deﬁned relative to the adopted ref- erence  crustal density of 2670 kg/m3 . Finally we compute and apply the primary indirect stripping eﬀect of the density contrast (relative to the mantle) of the reference  crust. The constant value  of −520 kg/m3  is adopted for this density contrast relative to the mantle. All data  are evaluated on a 1 × 1 arc-deg  geographical grid.  The complete  crust-stripped geoidal  undulations, globally having  a range  of approximately 1.5 km, contain  the gravi- tational signal  coming from the global  mantle  lithosphere (upper mantle) morphology and density composition, and  from the sub-lithospheric density heterogeneities. Large  errors in the complete  crust-stripped geoid are expected due to uncertainties of the CRUST 2.0 model, i.e., due to deviations of the CRUST 2.0 model density from the real earth’s crustal density and due to the Moho-boundary uncertainties.